Функції теорії міжнародних відносин - Чеканов, Всеволод Юрійович (My University, 2013)
У статті розглядається практично недосліджена проблема місця різних функцій теорії міжнародних відносин як наукової дисципліни. Поданий історичний нарис спроб застосування теорії ігор та інших математичних і статистичних методів з метою збільшення точності прогнозів, а також спроб зміни співвідношення практичної і теоретичної функцій даної дисципліни. The article deals with almost unexplored problem of the place of various functions within the international relations’ theory as science. The given research is important to make the international relations’ theory more connected with the changing realities of post bipolar world. The article contains the overview of the problem seen not from the inside of the discipline but from the impartial view point out of its structural framework. Thus it provides the position completely different from usually present in the researches of the specialists. It represents also a historical sketch of the attempts to use the theory of games and other mathematical and statistical methods to increase the preciseness of forecasts as well as a sketch of attempts to change the balance of practical and theoretical functions of the discipline.
Keywords: функція; наукова дисципліна; теорія міжнародних відносин; прогнозування; function; scientific discipline; international relations’ theory; forecasting